The Concept of Love in Islam, Christianity, and Judaism for the Postmodern Indonesian Religious Communities - Anggi Maringan Hasiholan; Aldi Abdillah (Jurnal Dialog, 2022)
The pattern of thinking relativism and pluralism in the postmodern era has always been a problem in religious life. The problem is due to the openness of relations between religions. This thinking style will be good if it accommodates a sense of brotherhood and mutual understanding between religious communities. On the other hand, it will be harmful if it is used to bring down other religions. This study aims to build a constructive model of comparative theology in a pluralistic society in Indonesia. The research method used in this paper is comparative theology by comparing the concept of Habluminallah-Habluminannas, with a similar idea in Christianity, which is also rooted in Judaism. The results showed that the idea of Habluminallah-Habluminannas is a unifying difference from the three Abrahamic religious concepts without eliminating the religiosity of each religion. This study concludes that Habluminallah-Habluminannas is the shade of the three Samawi religions to strengthen harmony and brotherhood. Keywords: habluminallah-habluminannas, comparative theology, inter-religious dialogue, postmodern